An intervention to improve pneumococcal vaccination uptake in high risk 50-64 year olds vs. expanded age-based recommendations: an exploratory cost-effectiveness analysis - Angela R. Wateska; Mary Patricia Nowalk; Chyongchiou J. Lin; Lee H. Harrison; William Schaffner; Richard K. Zimmerman; Kenneth J. Smith (Taylor & Francis Group, 2019)
In the U.S., pneumococcal polysaccharide vaccine (PPSV23) uptake among high-risk adults aged <65 years is consistently low and improvement is needed. One barrier to improved vaccine coverage is the complexity of the adult vaccination schedule. This exploratory analysis compared the cost-effectiveness of strategies to increase pneumococcal vaccine uptake in high-risk adults aged 50-64 years. We used a Markov model to compare strategies for non-immunocompromised 50-64 year olds: 1) current pneumococcal polysaccharide vaccine (PPSV23) recommendations; 2) current recommendations enhanced by an intervention; 3) PPSV23 plus pneumococcal conjugate vaccine (PCV13) for high-risk patients with no intervention; or 4) both vaccines for all 50-year-olds with no intervention. Parameters included CDC data and other US data, varied extensively in sensitivity analyses. In the analysis, vaccinating high-risk individuals with PPSV23/PCV13 was the least costly strategy, with total costs of $424/person. Vaccinating all 50 year olds with PPSV23/PCV13 cost $40 more and gained 0.00068 quality-adjusted life years (QALY), or $57,786/QALY gained. Current recommendations with or without an intervention program were more expensive and less effective than other strategies. In multi-way sensitivity analyses, the current recommendations/intervention program strategy was favored at a $100,000/QALY threshold only if non-bacteremic pneumococcal pneumonia rate or PCV13 serotype coverage were substantially lower than base case values. Thus, an intervention program to improve pneumococcal vaccine uptake among high-risk 50-64 year-olds was not cost-effective in most scenarios. High-risk individuals receiving both PCV13 and PPSV23 could be economically favorable, and vaccinating all 50-year-olds with both vaccines could be considered.